2012
DOI: 10.1161/circep.112.975425
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Glibenclamide-Sensitive ATP-Sensitive K + Channels During β-Adrenergically Induced Metabolic Stress Produces a Substrate for Atrial Tachyarrhythmia

Abstract: channels activate in response to β-adrenergic metabolic stress in Langendorffperfused rat hearts, resulting in a proarrhythmic substrate. (Circ Arrhythm Electrophysiol. 2012;5:1184-1192.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
2
9
2
Order By: Relevance
“…The inwardly rectifying current was effectively abolished on removal of external K + , consistent with the contributions of inwardly rectifying K + channels (K ir ) to I K1 (Hibino et al., 2010; Yan et al., 2005). Note that while the strong inward rectification of I K1 recorded from LA and PV cardiomyocytes is consistent with a major contribution of K ir 2.x in either cell type, in principle, constitutively active G‐protein‐gated K ir 3.x channels and ATP‐sensitive K ir 6.x/SURx (K ATP ) channels may also have contributed to the K + e ‐sensitive inwardly rectifying currents in the present study (Ehrlich et al., 2004; Hibino et al., 2010; Kim et al., 2012). In addition, a component of I Kss , evident at positive potentials using the ramp protocol, was also inhibited by removal of external K + .…”
Section: Resultssupporting
confidence: 89%
“…The inwardly rectifying current was effectively abolished on removal of external K + , consistent with the contributions of inwardly rectifying K + channels (K ir ) to I K1 (Hibino et al., 2010; Yan et al., 2005). Note that while the strong inward rectification of I K1 recorded from LA and PV cardiomyocytes is consistent with a major contribution of K ir 2.x in either cell type, in principle, constitutively active G‐protein‐gated K ir 3.x channels and ATP‐sensitive K ir 6.x/SURx (K ATP ) channels may also have contributed to the K + e ‐sensitive inwardly rectifying currents in the present study (Ehrlich et al., 2004; Hibino et al., 2010; Kim et al., 2012). In addition, a component of I Kss , evident at positive potentials using the ramp protocol, was also inhibited by removal of external K + .…”
Section: Resultssupporting
confidence: 89%
“…Most studies of cardiac arrhythmias resulting from myocardial ischaemia have been focused predominantly on the abnormalities of ventricular rhythm and relatively little is known about the role of K ATP channels in abnormal atrial rhythm. A recent study has shown that activation of K ATP channels by β‐adrenoceptor‐induced metabolic stress provides a substrate for atrial tachyarrhythmias in mouse isolated heart (Kim et al ., ). In support, pinacidil shortens atrial AP duration and increases arrhythmia inducibility in human right atrial and right ventricular wall (Fedorov et al ., ).…”
Section: Pathophysiological Function Of Katp Channels In the Cardiovamentioning
confidence: 97%
“…Studies have also investigated arrhythmia inducibility in atrial preparations. In a rat model β-adrenergic induced metabolic stress caused reduced intracellular ATP concentration and led to inducible atrial tachyarrhythmia that was reversed with glibenclamide (279). In a murine model with salt-induced hypertension, atrial K ATP channel upregulation was seen coinciding with a shortened effective refractory period and increased atrial arrhythmia inducibility (300).…”
Section: Cardiac Arrhythmiamentioning
confidence: 99%